"A person who does not have money does not enter": a qualitative study on refugee women's experiences of respectful maternity care - Tamar Kabakian-Khasholian; Jihad Makhoul; Aleni Ghusayni (BMC, 2022)
Abstract Background Women's childbirth experiences in health facilities is at the core of quality of care. Their perceptions of poor-quality care, including disrespectful care at health facilities during childbirth, is recognized as a significant barrier to seeking care for subsequent births. Research that explores women's perspectives of the dimensions of disrespect and mistreatment during childbirth in Arab countries is scarce, and there is none pertaining to refugee groups who carry the burden of multiple vulnerabilities and who suffer from discontinued care, especially in fragile health systems. This paper aims at presenting Palestinian, Iraqi and Syrian refugee women's experiences, understanding and interpretation of disrespect and mistreatment during childbirth in hospitals in Lebanon. Methods This study employed phenomenology, a qualitative research design to generate data through in-depth interviews. Women who were 3 to 6 months postpartum were recruited through the non-governmental organizations (NGOs) that are actively engaged in providing welfare and healthcare services to different populations of refugee women in Lebanon. In total, 24 women were interviewed. All interviews were audio recorded, transcribed verbatim and subjected to thematic analysis. Results Of the 24 women who participated in this study, 9 were Palestinian, 12 were Syrian and 3 were Iraqi. The participants spoke of restricted choices to hospitals, care providers and to types of birth, while revealing adverse experiences during childbirth in healthcare facilities, including verbal and physical abuse, disrespectful verbal and non-verbal communication by healthcare providers. They also reported sub-standard care, denial of birth companions and breaches to their privacy. Our findings exemplify how the coverage of the cost of facility-based births by UN agencies and NGOs increase refugee women's vulnerability to disrespect and mistreatment during childbirth. Conclusion This study shows how disrespect and mistreatment are intertwined in a complex system which is devised to ensure access to facility-based birth for displaced populations. Implications for programs and policies point to the need for strengthening capacity and for providing resources for the adaptation of global guidelines into context-specific strategies for the provision of quality maternity care during humanitarian crises and beyond.